AN ANALYSIS OF FIRST YEAR STUDENTS’ GRAMMATICAL ERROR IN NARRATIVE TEXT, STIBA SARASWATI DENPASAR - Rahmanu, I Wayan Eka Dian (Institut Hindu Dharma Negeri Denpasar, 2019)
Structure is improbable separated with the English literature and this concept should be simply applied for linguists or apprentices in English for Foreign Language and English for Second Language as well. However, in the process of presenting the text using grammar, pupils tend to make inaccurate comprehension frequently. So in this occasion, the researcher analyzed the learners’ grammar mistakes in written text through narrative of 31 apprentices in STIBA Saraswati Denpasar. The method in delivering the result of this article used qualitative research which discovered and explained students’ inaccurate grammar on some typical of structure. The final achievement found by the writer was that more than 50% sample of texts had mistakes on past sentences while the least number of grammar mistakes which on present perfect, simple past: be, preposition plural – singular, modal, gerund, to infinitive, passive voice and subject pronouns were slightly under 49%.